Environment and Co-occurring Native Mussel Species, but Not Host Genetics, Impact the Microbiome of a Freshwater Invasive Species (Corbicula fluminea) - Chiarello, Marlène; Bucholz, Jamie R.; McCauley, Mark; Vaughn, Stephanie N.; Hopper, Garrett W.; Sánchez González, Irene; Atkinson, Carla L.; Lozier, Jeffrey D.; Jackson, Colin R. (Frontiers in Microbiology, 2022)
The Asian clam Corbicula fluminea (Family: Cyneridae) has aggressively invaded freshwater habitats worldwide, resulting in dramatic ecological changes and declines of native bivalves such as freshwater mussels (Family: Unionidae), one of the most imperiled faunal groups. Despite increases in our knowledge of invasive C. fluminea biology, little is known of how intrinsic and extrinsic factors, including co-occurring native species, influence its microbiome. We investigated the gut bacterial microbiome across genetically differentiated populations of C. fluminea in the Tennessee and Mobile River Basins in the Southeastern USA and compared them to those of six co-occurring species of native freshwater mussels. The gut microbiome of C. fluminea was diverse, differed with environmental conditions and varied spatially among rivers, but was unrelated to host genetic variation. Microbial source tracking suggested that the gut microbiome of C. fluminea may be influenced by the presence of co-occurring native mussels. Inferred functions from 16S rRNA gene data using PICRUST2 predicted a high prevalence and diversity of degradation functions in the C. fluminea microbiome, especially the degradation of carbohydrates and aromatic compounds. Such modularity and functional diversity of the microbiome of C. fluminea may be an asset, allowing to acclimate to an extensive range of nutritional sources in invaded habitats, which could play a vital role in its invasive success.